Pendekatan Kaidah Fikih dalam Konteks Hukum Islam Kontemporer : (Kajian Prinsip Kehati-hatian, Kemaslahatan, dan Keringanan) - Muhammad Ulil Albab; Tutik Hamidah (LPPI Universitas Al-Qolam Malang, 2024)
The rules of fiqh are fundamental principles in Islamic law that provide guidance in resolving complex legal issues, especially in modern social, economic, and political contexts. This article examines the relevance of four main rules of fiqh, namely: (1) If halal and haram come together, then haram defeats halal; (2) If two mafsadat conflict, then the lesser harmful one is prioritized; (3) Policies towards the people must be based on the public interest; (4) The easy is not defeated by the difficult. This study attempts to analyze the application of these rules in a contemporary context through an analytical-descriptive approach to classical and modern literature. The results of the study show that these rules are not only universal, but also adaptive in facing the dynamics of the times. The first rule is relevant in the regulation of halal-haram in the halal industry and sharia economy. The second rule contributes to mafsadat mitigation policies on health issues and public law. The third rule provides a normative basis for policies based on public interest, such as the distribution of zakat and productive waqf. The fourth principle reflects the flexibility of sharia in the obligation of worship and muamalah. The novelty of this article lies in the integration of fiqh principles with specific case studies in the modern era and the offering of an applicative framework based on maqashid sharia that is in line with the sustainable development goals (SDGs). These findings are expected to contribute to the development of Islamic law that is relevant and responsive to global needs.